EN UTREDNINGS FORVENTNINGER - FORTIDENS FREMTIDING AV EN DATADREVET FORVALTNING. - Eckhoff, Torjus Solheim (Kulturstudier, 2024)
This article examines how a Norwegian o#cial report (NOU), a public enquiry, published in 1978 projects a future administration in which a data infrastructure will have an increasingly important function. Through a practice-oriented document analysis and a theoretical framework for futuring, the paper explores questions about what kind of expectations the enquiry has for computer technology and the conditions on which these expectations are based. It shows how the enquiry is futuring that new computer technology would enable a distributed and agile public administration. This analysis contributes to a reflection on how collective ideas and socio-technical desires are created in the meeting point between di!erent conditions, actors and technologies. It also points towards a more critical approach to contemporary expectations of future computer technology and what it can achieve, expectations that should be seen in relation to past futures.